Expression of microRNAs, miR‐21, miR‐31, miR‐122, miR‐145, miR‐146a, miR‐200c, miR‐221, miR‐222, and miR‐223 in patients with hepatocellular carcinoma or intrahepatic cholangiocarcinoma and its prognostic significance. Issue 4 (27th December 2011) - Karakatsanis, Andreas; Papaconstantinou, Ioannis; Gazouli, Maria; Lyberopoulou, Anna; Polymeneas, George; Voros, Dionysios
Abstract MicroRNAs are a class of non‐coding molecules found to regulate a variety of cellular functions in health and disease. Dysregulation of microRNAs is involved in liver disease, especially hepatocarcinogenesis. Since primary hepatic malignancies are typically characterized by late diagnosis, frequent recurrence, and poor response to adjuvant therapy, there is a need for the discovery of novel biomarkers in order to achieve earlier diagnosis, predict tumor aggressiveness and response to adjuvant therapy. The purpose of this study is to evaluate the expression of certain microRNAs (miR‐21, ‐31, ‐122, ‐145, ‐146a, ‐ 200c, ‐221, ‐222 and ‐223) in patients with hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICC), as well as to assess their prognostic significance. Micro‐RNA expression was assessed by reverse transcription and real‐time PCR (RT‐PCR). Clinicopathological data and survival rates were retrieved and analyzed. According to our results, miR‐21, miR‐31, miR‐122, miR‐221, miR‐222 were significantly up‐regulated in HCC tissues, whereas miR‐145, miR‐146a, miR‐200c, and miR‐223 were found to be down‐regulated. Concerning ICC samples, miR‐21, miR‐31, and miR‐223 were found to be over‐expressed, whereas miR‐122, miR‐145, miR‐200c, miR‐221, and miR‐222 were down‐regulated. Additionally, expression of miR‐21, miR‐31, miR‐122, and miR‐221 in HCC correlated with cirrhosis, while miR‐21 and miR‐221 associated with tumor stage and poor prognosis. In ICC tissues, miR‐21, miR‐31, and miR‐223 were found to be over‐expressed, but no correlation with clinicopathological features was found. © 2011 Wiley Periodicals, Inc.